Husband and Wife Relations in Javanese Society Perspective of Legal Theory as a Manifestation of the Nation's Soul (national spirit) - Setyobudi, Teguh; Wahid, Ziadul Ulum; Makky, Aisyunnada (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research examines husband and wife relations in Javanese society using the perspective of legal theory as a manifestation of the national spirit, known as Volksgeist. The relationship between husband and wife can be understood as a reflection of cultural values and the collective spirit of society which emphasizes harmony, balance of roles and spirituality and prioritizes the involvement of the extended family in maintaining traditional values. This research shows that these relationships are often based on the principle of complementarity, where both parties contribute to creating inner harmony within the family. However, social changes triggered by urbanization, education, and globalization encouraged the adaptation of Volksgeist values to modern norms. So a legal formation process is needed that absorbs local wisdom and cultural values to create regulations that are relevant to the needs of society. The incarnation of law is needed as a link between tradition and modernity. In conclusion, husband and wife relations from the Volksgeist perspective reflect cultural values that prioritize harmony and balance of roles, but still adapt to the social changes that occur. Law as a manifestation of the national spirit plays an important role in maintaining the continuity of cultural values while providing contextual justice in husband and wife relationships.